2019
DOI: 10.2298/sos1903327a
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, wear and corrosion properties of NiB-TiC composite materials produced by powder metallurgy method

Abstract: In this study, NiB-TiC composite materials were produced using powder metallurgy. In the Ni-TiC-B powder mixture, TiC was fixed at a rate of 5 %, 5, 10 and 15 % boron was added and mechanical alloying was carried out. The prepared powder mixtures were cold pressed under pressure of 400 MPa and sintered in an argon atmosphere at 800 o C for 2 hours. Microstructure, phase formation, hardness, wear and corrosion properties of the samples were investigated in detail. Scanning electron microscopy (SEM) was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As a result of studies conducted on the mechanical and tribological performance of the hybrid composites they produced, Devaganesh and colleagues noted that the wear rate in the material produced as Al7075 + 5 % SiC+5 % hBN was the lowest [21]. A SEM investigation was used to determine wear mechanism of experiment samples in especially most wear articles [22]. As a result of sintering and wear testing applications, the obtained SEM images of the wear surface of AA 7075 aluminum material are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of studies conducted on the mechanical and tribological performance of the hybrid composites they produced, Devaganesh and colleagues noted that the wear rate in the material produced as Al7075 + 5 % SiC+5 % hBN was the lowest [21]. A SEM investigation was used to determine wear mechanism of experiment samples in especially most wear articles [22]. As a result of sintering and wear testing applications, the obtained SEM images of the wear surface of AA 7075 aluminum material are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the measured corrosion current values, the smallest value belongs to copper‐nickel+boron carbide sample (106 μA cm −2 ). In corrosion science, the general approach to corrosion is that low corrosion current and high corrosion potential means low corrosion rate or high corrosion resistance [14–16]. According to this approach, it is the copper‐nickel+10 % silicon carbide sample which is the most resistant to corrosion among the composites.…”
Section: Resultsmentioning
confidence: 99%
“…The parts produced by this method have a less rough surface than the parts produced by other methods and often do not require secondary processing. Homogeneous distribution of the quality, completely controllable ingredient and content, and low unit cost make powder metallurgy as a unique production method in the production industry [8][9][10][11][12][13]. Thus, it was found that approximately 97 % of the material was used in mass production with PM.…”
Section: Introductionmentioning
confidence: 99%